2013
DOI: 10.1111/jcmm.12118
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative role of endogenous leucotrienes and platelet‐activating factor in ischaemia–reperfusion‐mediated tissue injury

Abstract: Insufficient oxygen delivery to organs leads to tissue dysfunction and cell death. Reperfusion, although vital to organ survival, initiates an inflammatory response that may both aggravate local tissue injury and elicit remote organ damage. Polymorphonuclear neutrophil (PMN) trafficking to remote organs following ischaemia/reperfusion (I/R) is associated with the release of lipid mediators, including leucotriene (LT) B4, cysteinyl-LTs (CysLTs) and platelet-activating factor (PAF). Yet, their potentially cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…found that leukotrienes and platelet activating factor (PAF) are important inflammatory mediators that play critical roles in developing microvascular inflammatory response to ischemia‐reperfusion induced by HS and FR (Bitencourt et al. ). Park et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that leukotrienes and platelet activating factor (PAF) are important inflammatory mediators that play critical roles in developing microvascular inflammatory response to ischemia‐reperfusion induced by HS and FR (Bitencourt et al. ). Park et al.…”
Section: Discussionmentioning
confidence: 99%
“…As an antioxidant, ubiquinol decreases ROS levels in the mesenteric microcirculation, thus potentially inhibiting the synthesis and expression of the transcription-dependent adhesion molecule. Bitencourt et al found that leukotrienes and platelet activating factor (PAF) are important inflammatory mediators that play critical roles in developing microvascular inflammatory response to ischemia-reperfusion induced by HS and FR (Bitencourt et al 2013). Park et al found that the release of PAF promoted leukocyte adherence and also stimulated increased generation of ROS especially superoxide from leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Inflitration of white blood cells from circulatory system is essential during inflammatory responses [ 9 , 10 ]. A group of chemotactic agents such as microbial endotoxins holding amino terminal N-formyl methionyl groups, C5a complement fragment, and interleukins along with the secretions of basophils such as platelets activating factor, histamine, and leukotriene B can stimulate intense leukocytes infiltration within few minutes [ 11 , 12 ]. Among the leukocytes, neutrophils are the first inflammatory cells that are recruited at the acute inflammation site [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current anti-inflammatory therapies mainly target the formation and action of inflammatory mediators including LTB4 [ 10 , 11 ]. Consequently, current LTB4-targeting drugs interrupt the progressive recruitment and sustained activation of neutrophils within infarcted myocardium [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%